Facility logistics approaches and solutions to next generation challenges - Lahmar, Maher (Series on resource management., 2008)
The book first discusses the main trends impacting facility logistics operations, including visibility, security, flexibility, labor, globalization, and sustainability. It then examines the functionalities and capabilities of warehouse management systems (WMS) and outlines a comprehensive yet simple method for the quick assessment of warehouse performance. The following chapters present a set of solutions to emerging challenges in the design and management of facility logistics, along with procedures to better plan and manage the logistics activities within a production or storage facility. The final chapter reviews educational resources and offers examples of how multimedia tools can be used to develop new teaching material.